2009
DOI: 10.1017/s0007114509993138
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment methods for intakes of iron, calcium, selenium, zinc and iodine

Abstract: The EURopean micronutrient RECommendations Aligned (EURRECA) Network of Excellence is working towards developing aligned micronutrient recommendations across Europe. The purpose of the present study was to conduct a review of methods used in validation studies carried out in adults assessing dietary intake of EURRECA priority minerals. A search strategy and inclusion criteria were defined and a scoring system was developed to rate the quality of each validation study that produced a quality index with possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 105 publications
1
72
0
2
Order By: Relevance
“…9 A number of approaches can be used to estimate the dietary intake of Se, ranging from direct analysis of composite food types, to indirect calculation using dietary or market basket surveys and food composition tables. 13 Notably, since the total concentration of Se in food strongly reflects the soil conditions, the dietary intake varies widely with geographical localization. 14 An additional crucial aspect is that food types provide Se in distinct combinations of chemical forms which in turn entail a different bioavailability of the element.…”
Section: Selenium In Foodmentioning
confidence: 99%
“…9 A number of approaches can be used to estimate the dietary intake of Se, ranging from direct analysis of composite food types, to indirect calculation using dietary or market basket surveys and food composition tables. 13 Notably, since the total concentration of Se in food strongly reflects the soil conditions, the dietary intake varies widely with geographical localization. 14 An additional crucial aspect is that food types provide Se in distinct combinations of chemical forms which in turn entail a different bioavailability of the element.…”
Section: Selenium In Foodmentioning
confidence: 99%
“…The selection of an appropriate reference method is an essential element of the effective assessment of FFQs and research in this area is often hampered by the lack of a gold standard for dietary intake 18 . Furthermore, error detection methods should be as independent as possible 19,20 .…”
Section: Validitymentioning
confidence: 99%
“…The main sources of error in FFQs are participant memory, the interpretation of questions, perception of serving sizes and the limitations imposed by a fixed list of food items. Open-ended diet records do not depend on memory and are likely to result in less correlated errors 1,18 . Nevertheless, keeping a diet record is a substantial burden on participants and often influences the respondent's diet.…”
Section: Validitymentioning
confidence: 99%
“…Following EURRECA's in depth review of all available dietary assessment validation studies, which analysed the utility of a range of dietary micronutrient intake questionnaires (Henriquez-Sanchez et al, 2009;Ortiz-Andrellucchi et al, 2009a;Ortiz-Andrellucchi et al, 2009b;OrtizAndrellucchi et al, 2009c;Øverby et al, 2009;Serra-Majem et al, 2009c), it was concluded that a scoring system was required to facilitate straightforward evaluation of the reliability of FFQ data . validation studies assessed, which reported data from at least one vitamin were also categorised into three groups dependent on the reference method or gold standard applied in each case.…”
Section: Quality Scoring Of Dietary Intake Datamentioning
confidence: 99%